Sleep restriction impairs item memory discrimination but not general recognition in young adolescents. - Saletin, Jared M; Moyles, Sinéad M; Dionisos, Victoria O; Christiansen, Taylor G; Sherman, Claire Mayew; Mason, Gina M; Bunge, Silvia A; Castellanos, Francisco Xavier; Owens, Judith; Barker, David H; Dickstein, Daniel P; Carskadon, Mary A (Sleep Advances, 2025)
Study Objectives The impact of sleep loss on memory encoding is well described in adults, yet less understood in youth, despite the prevalence and educational relevance of adolescent sleep loss. Here, we implement at-home sleep restriction in youth ages 10–14 and a well-validated hippocampus-dependent learning task to elucidate how real-world levels of sleep loss affect distinct memory encoding processes at this young age. Methods A within-subject cross-over design involved five nights of at-home sleep restriction (7.5 h in bed) compared to sleep optimization (10 h in bed). Restriction was achieved by delaying bedtime and advancing risetime equally. All sleep was monitored with wrist actigraphy, sleep diaries, and daily calls to the laboratory. Testing involved the validated Mnemonic Similarity Task (MST), which can distinguish between two components of successful memory encoding: general memory recognition for old items and "lure discrimination," a hippocampus-dependent ability to distinguish similar yet distinct items. Results As estimated by actigraphy, our manipulation reduced sleep by 1.4 ± 0.48 h per night for five nights. This reduction resulted in a selective deficit in MST-indexed memory encoding; we observed a decrease in lure discrimination (i.e. the ability to distinguish highly similar items), but no impact on recognition of old items. Conclusions We present evidence that low levels of sleep loss for five nights (typical of a school week) are sufficient to alter memory encoding in youth. We interpret these data in the context of classroom-based learning and speculate that reduced lure discrimination may yield memory that is less capable of distinguishing closely related facts and concepts. Statement of Significance Sleep loss impacts learning; however, most of this literature stems from adults. Despite the sleep loss experienced by youth as developmental pressures mix with early school-start-times, we know relatively little about how insufficient sleep at this age impacts learning. Here, we present a repeated-measures experiment in 10–14-year-old youth using an at-home sleep manipulation. We show five nights of sleep restriction (mirroring a typical school week by reducing time-in-bed from 10 to 7.5 h) alters hippocampus-dependent memory encoding with selectivity for discerning similar items from one another. We discuss these data in the context of a sleep and memory literature rooted in the career of Prof. Robert Stickgold and offer educational implications for this vulnerable time of life.